2021
DOI: 10.1177/01945998211000448
|View full text |Cite
|
Sign up to set email alerts
|

Sclerotherapy for Benign Cystic Lesions of the Head and Neck: Systematic Review of 474 Cases

Abstract: Objective The role of sclerotherapy for vascular lesions of the head and neck is well established. However, the efficacy of sclerotherapy for benign cystic lesions of the head and neck is less clear. The objective of this review is to determine the efficacy and safety of sclerotherapy for benign cystic lesions of the head and neck. Data Sources PubMed/MEDLINE, Cochrane Library, and Embase. Review Methods The PRISMA guidelines (Preferred Reporting Systems for Systematic Reviews and Meta-analyses) were followed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 58 publications
(62 reference statements)
0
10
0
2
Order By: Relevance
“…However, recent randomized clinical trials and meta-analyses have shown that sclerotherapy with OK-432 is less effective for plunging than for simple ranulas, with complete response rates of 25% to 67% in plunging ranula. [20][21][22] Additionally, there are drawbacks to OK-432, such as a slow therapeutic response that takes more than 6 weeks after treatment; complications, including swelling, pain, erythema, and fever 23 ; and the need to perform skin tests to determine allergies to penicillin G. 7 In our study, 90% of the patients had plunging ranulas and demonstrated outcomes comparable with those treated with OK-432. Because ethanol is a more potent and cost-effective sclerosing agent and induces a faster therapeutic response than OK-432, 1 ethanol may be an effective and safe sclerosant that can replace OK-432 for treating ranula.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…However, recent randomized clinical trials and meta-analyses have shown that sclerotherapy with OK-432 is less effective for plunging than for simple ranulas, with complete response rates of 25% to 67% in plunging ranula. [20][21][22] Additionally, there are drawbacks to OK-432, such as a slow therapeutic response that takes more than 6 weeks after treatment; complications, including swelling, pain, erythema, and fever 23 ; and the need to perform skin tests to determine allergies to penicillin G. 7 In our study, 90% of the patients had plunging ranulas and demonstrated outcomes comparable with those treated with OK-432. Because ethanol is a more potent and cost-effective sclerosing agent and induces a faster therapeutic response than OK-432, 1 ethanol may be an effective and safe sclerosant that can replace OK-432 for treating ranula.…”
Section: Discussionmentioning
confidence: 80%
“…Therefore, we also evaluated the risk factors associated with subsequent surgery as a secondary outcome. Eleven of the 57 patients (19%) underwent subsequent surgery after recurrence, a percentage similar to that of patients with plunging ranulas treated with OK-432 (20.8%) . Although PPS extension was not significantly associated with subsequent surgery, possibly due to the limited number of patients with PPS extension (n = 12), it makes the effective aspiration of all mucus materials and even distribution of the effects of ethanol across surrounding connective tissue more challenging in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent systematic review on the efficacy of sclerotherapy for benign cystic lesions of the head and neck reported complete and partial response rate of 60.5% and 27.9%, respectively. 14 It also noted that timing of sclerotherapy response was variable, with some changes occurring months after the initial injection. Moreover, the average patient needed approximately two sclerotherapy injections to achieve a response.…”
Section: Discussionmentioning
confidence: 99%
“…In view of the low overall patient number in this review, statistical analysis was not feasible to compare sclerotherapy versus only aspiration. A recent systematic review on the efficacy of sclerotherapy for benign cystic lesions of the head and neck reported complete and partial response rate of 60.5% and 27.9%, respectively 14 . It also noted that timing of sclerotherapy response was variable, with some changes occurring months after the initial injection.…”
Section: Discussionmentioning
confidence: 99%